Peran Program “Jumat Curhat” dalam Meningkatkan Citra Kepolisian Mojokerto Raya - Khoiru M Habibi; Rakhmad S. Ramadhani; Fatihatul L (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The police are currently a topic of conversation due to several problems caused by irresponsible members, resulting in a negative view of the police. To overcome this, a Quick Wins Presisi program was implemented, such as